2021
DOI: 10.1080/21655979.2021.2000224
|View full text |Cite
|
Sign up to set email alerts
|

Rotigotine protects against oxidized low-density lipoprotein(ox-LDL)-induced damages in human umbilical vein endothelial cells(HUVECs)

Abstract: Rotigotine is a non-ergoline dopamine agonist that has been licensed for the treatment of Parkinson’s disease. Cardiovascular diseases are the world’s leading cause of death. Ox-LDL- induced endothelial damages are involved in the initiation and progression of cardiovascular diseases. In this study, we assessed the beneficial properties of Rotigotine on ox-LDL-induced insults to HUVECs to highlight its potential use in the treatment of cardiovascular diseases. Our findings show that Rotigotine suppresses the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Moreover, when atherosclerotic injury occurs, endothelial cells release adhesion factors and attract monocytes to accumulate, which can reflect cell adhesion (35), and U937 is a human monocyte. U937 cells were used to detect the changes of HUVEC adhesion ability in the present study (36). It was found that NEDD4 overexpression led to a decrease in the levels of ROS, iNOS, VCAM-1, ICAM-2 and the number of U937-HUVEC adhesion cells, but an increase in the level of eNOS.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, when atherosclerotic injury occurs, endothelial cells release adhesion factors and attract monocytes to accumulate, which can reflect cell adhesion (35), and U937 is a human monocyte. U937 cells were used to detect the changes of HUVEC adhesion ability in the present study (36). It was found that NEDD4 overexpression led to a decrease in the levels of ROS, iNOS, VCAM-1, ICAM-2 and the number of U937-HUVEC adhesion cells, but an increase in the level of eNOS.…”
Section: Discussionmentioning
confidence: 71%
“…It was previously shown that the reduction of PLMS with rotigotine was significantly associated with a decrease in blood pressure (Bauer et al, 2016); however, lipid values were not measured. Of note, rotigotine attenuated cholesterol uptake in endothelial cells thus having an anti‐atherosclerotic effect (Kang et al, 2021). We hypothesised that increased MSNA is the reason for dyslipidaemia in PLMS.…”
Section: Discussionmentioning
confidence: 99%
“…The co-stimulation of both B2R and D2R receptors regulated the expression of markers of apoptosis such as Bcl-2, Bcl-xL, and Bax and inhibited the release of IL-6 and endothelin-1 [ 89 ]. In human umbilical vein endothelial cells, the D2-like receptor agonist rotigotine (D2R > D3R > D4R > D5R > D1R) inhibited NF-κB activation and reduced its reporter activity, exerting anti-inflammatory actions [ 90 ]. DA, receptor not determined, also regulated the interaction of leukocytes and the endothelium, decreasing the transendothelial migration of leukocytes and the expression of ICAM-1 and E-selectin in endothelial cells and attenuating the chemoattractant effect of IL-8 [ 91 , 92 ].…”
Section: Introductionmentioning
confidence: 99%